(untitled) (The International Journal for Scientific Research, 2024)
The study clearly focused on identifying the most preferred sports media from the point of view of the Saudi public, and measuring the extent of the Saudi public’s reliance on sports media in attracting sports information. It also focused on identifying the motives for the Saudi public’s follow-up of sports media. The study was based on a media survey using a questionnaire as a tool for taking data for the study. The study concluded with results, the most important of which is that the most preferred reasons that the Saudi public prefers to study the interactive study are electronic social networking sites, social networking sites, and then television channels. The popularity of the Saudi public, as well as the study of the Saudi sports media, was average. International sports news was the topics preferred by the Saudi public through sports media, followed by local sports news and then Al-Rida entertainment programs.